The Influence of Organizational Commitment on Job Satisfaction and its Implications for Turnover Intention In Teachers and Education Personnel of SMK PGRI 2 Salatiga - Wibowo, Mada Adi; Utomo, Hardi; Purwanti, Endang (ProBisnis : Jurnal Manajemen, 2024)
In the world of education, educators have an obligation to create an educational atmosphere that is meaningful, fun, creative/innovative, dynamic and has two-way communication, has a professional commitment to improve the quality of education and provides a role model by maintaining the reputation of the institution, profession and position in accordance with the beliefs given to the educators. This study aims to analyze the effect of Organizational Commitment on Job Satisfaction and its Implications for Turnover Intention. The sample in this study were teachers and educational staff at SMK PGRI 2, Salatiga. The analysis tool is path analysis / Path Analysis. This study shows the results that Job Satisfaction cannot mediate Organizational Commitment to Turnover Intention.